Great library events from planning to promotion to evaluation - Flaherty, Mary Grace, 1960- (Medical Library Association books., 2021)
"Here is an accessible guidebook for hosting successful library events. From the first steps of defining the scope of an event to finding funding, to marketing and publicizing, evaluating, reporting and using data to keep the program cycle going, this guide is full of practical examples and tools"--